The Effect of the Perception of Fast Fashion Issues on H&M's Brand Image on H&M Social Media Followers - Eni Saeni; RR Roosita Cindrakasih; Priandono Kusumo (Journal of Creative Power and Ambition (JCPA), 2026)
The growth of the fast fashion industry has accelerated clothing production and consumption, while also generating environmental concerns such as increasing textile waste, intensive resource use, pollution, and overconsumption. These issues are increasingly discussed on social media and may influence public perceptions of brands associated with fast fashion, including H&M. This study aims to examine the influence of perceptions of fast fashion issues on H&M brand image among H&M social media followers. The study employed a quantitative approach using a survey method. The respondents consisted of 110 individuals who met the research criteria: they knew H&M, had purchased and/or used H&M products, and had received information about fast fashion. Data were collected through a Likert-scale questionnaire and analyzed using descriptive analysis, validity testing, reliability testing, simple linear regression, and a t-test. The results indicate that the research instruments demonstrated very high reliability. The regression analysis produced a coefficient of determination (R²) of 0.518, indicating that perceptions of fast fashion issues explained 51.8% of the variance in H&M brand image. The hypothesis test yielded a significance value of < 0.001, indicating a significant influence between perceptions of fast fashion issues and H&M brand image. These findings suggest that environmental issues associated with fast fashion are among the factors that should be considered in shaping brand image in the digital public sphere.